Factors Related to Anemia among Pregnant Women Attending Antenatal Clinic in Yala Province - Pattanasombutsook, Maneeratsami; Korwiwatanagarn, Suwannee; Siriphan, Siriphan (Princess of Naradhiwas University Journal, 2021)
This descriptive research aimed to investigate relationship among personal factors, obstetric history, knowledge about anemia and anemia of pregnant women, and to compare knowledge about anemia between anemia pregnant women and non-anemia pregnant women. The sample were 190 pregnant women attending antenatal clinic at Health Promotion Hospital, Health Promotion Center Number 1 in Yala province from February to August 2019. A convenience sampling with inclusion criteria was applied. Demographic data recording, obstetric history recording and knowledge about anemia were used to collect data. The content validity of the knowledge about anemia was between 0.67 and 1.00 based on IOC which was verified by three experts. The reliability was 0.7 based on KR-20. Data were analyzed using frequency, percentage, mean, standard deviation, Chi-square test, Crammer’s Contingency Coefficient and t-test. The findings revealed that anemia in previous pregnancy, inadequate intake of iron supplement, and gravidity were statistically significantly related to anemia (.275, .200, and .141, respectively) at p < .001, .005, and .05, respectively. Age, level of education, income, menstruation period, thalassemia carrier, interpregnancy interval, initiation of antenatal care, adequate antenatal care visit, and knowledge about anemia were not related to anemia. Knowledge about anemia between anemia pregnant women and non-anemia pregnant women was not different. The results of this study can be used as basic information to develop care model for anemia pregnant women.